Adolescents with type 1 diabetes’ perspectives on digital health interventions to enhance health literacy: a qualitative study - Naef, Aurélia Naoko; Fischbock, Nadine; Tezcan-Güntekin, Hürrem; Amelung, Volker Eric (Frontiers in Public Health, 2024)
Introduction Digital health intervention offers the potential to enhance health literacy, which is crucial for effective diabetes management, especially among adolescents. Diabetes is a major global public health issue, leading to devastating complications and increasing mortality rates. The incidence of type 1 diabetes mellitus (T1DM) is also on the rise, particularly among adolescents, necessitating multisectoral strategies to combat this disease. This study explores the perceptions of adolescents with T1DM in Germany regarding digital health interventions, with the aim of improving healthcare by addressing specific needs and guiding future research. Methodology This study employed a qualitative approach using semi-structured individual interviews with adolescents with T1DM (n = 20) aged 14 to 18 years old in Germany to explore their perspectives on digital interventions for health literacy promotion. The study adopted content analysis according to Kuckartz et al. and the research followed the Consolidated Criteria for Reporting Qualitative Research (COREQ) checklist. Ethical considerations were paramount and data were rigorously analyzed using coding and iterative processes to ensure data quality and reliability. Results The findings indicate that within three prominent domains, namely the utilization of digital health intervention for accessing and comprehending information, facilitating peer-to-peer interactions, and enhancing physician-patient communication and interaction, digital health interventions are either underutilized or insufficiently deployed. In addition, a notable observation is the apparent lack of patient-centered approaches for adolescents with T1DM in relation to digital health interventions and health literacy. Conclusion In order to enhance the utilization of digital health interventions and enhance health literacy it is essential to focus on capacity building through a patient-centered approach, to promote digital health literacy, and foster the cultivation of a participatory culture. The outcomes of this study offer valuable insights that can inform practical applications, further research endeavors, and influence policymaking.